1995
DOI: 10.1002/bit.260460608
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm parameters influencing biocide efficacy

Abstract: The influence of biofilm areal cell density, species composition, and the presence of abiotic particles on the disinfection and removal of bacterial biofilms by monochloramine was investigated. Mono- and binary population biofilms of Pseudomonas aeruginosa and Klebsiella pneumoniae were grown on stainless-steel slides in a continuous flow annular reactor. Biofilms were treated in the reactor with a pulse/step dose of 4 mg/L monochloramine for 2 h. Biofilm samples were disaggregated and assayed for colony forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Conversely, the deposition of calcite particles onto the biofilm surface hindered solute transport and decreased chlorine killing. The latter observation is consistent with the findings of a previous study showing that the deposition of calcite and clay particles decreased the susceptibility of biofilms to biocides (36). Further, we previously observed that in situ biomineralization of calcite occurs throughout the biofilm, while abiotically precipitated particles deposit onto the biofilm surface (29).…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the deposition of calcite particles onto the biofilm surface hindered solute transport and decreased chlorine killing. The latter observation is consistent with the findings of a previous study showing that the deposition of calcite and clay particles decreased the susceptibility of biofilms to biocides (36). Further, we previously observed that in situ biomineralization of calcite occurs throughout the biofilm, while abiotically precipitated particles deposit onto the biofilm surface (29).…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that specific bacterial subpopulations may occur, persist and spread within the systems as demonstrated for staphylococci by PFGE. Such observations indicate the possibility that these bacteria may survive in biofilm communities (Sharma & Anand 2002), in which increased levels of resistance to disinfectants have been recorded (Brooks & Flint 2008), and where the disinfectant efficacy could be adversely affected by the cell population density (Srinivasan et al 1995). e. coli, which was rarely found on the inside surfaces, originated mainly from such highly contaminated surface sites.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies have found that deposition of solid particles alters biofilm morphology (43,44). It has been suggested that this process should increase biofilm resistance to biocides by reducing transport of solutes into and within biofilms (45), but this hypothesis has not been tested experimentally. Calcium carbonate precipitation has also been found to increase the rigidity and strength of aerobic granules, which are biofilm-like suspended aggregates of cells encased in a matrix (21).…”
mentioning
confidence: 99%